The Cardenolide Glycoside Acovenoside A Affords Protective Activity in Doxorubicin-Induced Cardiotoxicity in Mice - Ezzat, Shahira M.; El Gaafary, Menna; El Sayed, Abeer M.; Sabry, Omar M.; Ali, Zeinab Y.; Hafner, Susanne; Schmiech, Michael; Jin, Lu; Syrovets, Tatiana; Simmet, Thomas (The Journal of pharmacology and experimental therapeutics, 2016)
The current study aimed to investigate the protective effect of the cardenolide glycoside acovenoside A (AcoA) against doxorubicin-induced cardiotoxicity in mice. AcoA was isolated from the pericarps of Acokanthera oppositifolia to chemical homogeneity and characterized by means of one- and two-dimensional nuclear magnetic resonance spectroscopy. AcoA exhibited relatively low toxicity in mice (LD50 = 223.3 mg/kg bw). Repeated administration of doxorubicin induced cardiotoxicity manifested by reduced activity of myocardial membrane-bound ion pumps and elevated serum biomarkers of myocardial dysfunction, oxidative stress, and inflammation. Pretreatment of doxorubicin-exposed mice with AcoA (11.16 or 22.33 mg/kg bw, i.p.) for 2 weeks after 2 weeks of combined administration of AcoA and doxorubicin protected the animals dose dependently against doxorubicin-induced cardiotoxicity as indicated by normalization of the levels of different myocardial markers of oxidative stress (malondialdehyde, nitric oxide, total antioxidant capacity, and cardiac glutathione), serum myocardial diagnostic marker enzymes (serum cardiac troponin T, creatine kinase isoenzyme MB, aspartate aminotransferase, and lactate dehydrogenase), and inflammatory markers (c-reactive protein, tumor necrosis factor-α, and interleukin-6), as well as myocardial Na+/K+-ATPase activity. These effects were attributed to the negative impact of AcoA on transcription factors nuclear factor κB and interferon regulatory factor 3/7. Thus acovenoside A might act as a cardioprotective agent to prevent doxorubicin-induced cardiotoxicity.